73 Nutritional impact of excluding red meat from the Canadian diet. (30th November 2020) - Gunte, Kebebe E; White, Robin R; Aukema, Harold; McAllister, Tim A; Riediger, Natalie; Legesse, Getahun; McGeough, E J; Wittenberg, Karin; Ibrahim, Naser; Ominski, Kim
Abstract: Foods of animal origin, including beef, pork, and lamb, provide macro- and micro-nutrients which may be difficult to obtain in adequate quantities from plant-based foods alone. Nonetheless, recent literature suggests that a shift away from red meat in favor of plant-based diets can reduce household greenhouse gas emissions without adversely affecting nutrient intake. The objective of the current study was to examine the nutrient intake of consumers who eliminated red meat from their diet, compared with those who did not. The impact of red meat elimination on nutrient intake was estimated using inverse probability weighting with regression adjustment estimator and bias-corrected matching estimators, using data garnered from the 2015 Canadian Community Health Survey. We also examined if self-selected diets without red meat fulfilled the Recommended Daily Allowance (RDA) of macronutrients, vitamins, and minerals, included in Canada's Dietary Reference Intake Tables. Adequate Intake (AI) was used when RDA could not be determined. Consumers who eliminated red meat from their diet reported significantly lower intake of several nutrients, including total saturated fatty acids, saturated 18:0 octadecanoyloxy fatty acid, protein, riboflavin, niacin, vitamins D, B6 and B12, and zinc, as compared with those who did not. Eliminating red meat also resulted in lower dietary cholesterol and sodium intake. Further, consumers who eliminated red meat reported mean daily intake levels below the daily requirements of Calcium, Magnesium, Potassium, and Vitamins A, B6 and D. The results from this study suggest that elimination of red meat may lead to dietary substitutions that result in nutritional deficiencies for Canadian consumers.